우선순위검색을 지원하는 고객맞춤형 병원 CRM시스템 설계 - 한정수(Jung-Soo Han); 김귀정(Gui-Jung Kim) (한국콘텐츠학회 논문지, 9(11), 2009)
This paper is focused on the medical CRM system design for a hospital custom management. CRM systems provides information and seminars to whom are necessity. For this, priority retrieval and similarity retrieval are able to be in the personnel order and the regional. The customer receives the message which sends out from the hospital, The hospital manages the message which reveals a participation intention in the seminar at real-time. The hospital grasps the participation degree of the seminar where the customer will participate and manages the patients who participate to the seminar actively, and when the next seminar will be hold, we designed the system able to provide the service as early as possible. 본 연구는 병원고객관리를 위한 의료용 CRM 시스템의 설계를 목적으로 한다. 본 CRM 시스템은 병원에서 제공하는 정보 및 세미나를 필요로 하는 환자들의 우선순위 검색과 이를 통해 검색 결과 내의 인원별, 지역별 등의 연관 검색이 가능하도록 하였다. 고객은 병원에서 발송한 메시지를 받고, 세미나에 참여의사를 밝히는 메시지를 병원에서 실시간으로 출력하고 이를 관리한다. 이를 통해 병원에서는 고객이 참가할 세미나의 참여도를 파악하고, 세미나에 적극적으로 참여하는 환자들을 별도로 관리하여 향후 세미나 개최 시 우선적으로 서비스를 제공할 수 있도록 설계하였다.